Case reports and case series in prehospital emergency care research. Issue 11 (23rd September 2010) - Patterson, P Daniel; Weaver, Matthew; Clark, Sunday; Yealy, Donald M
Abstract : Research begins with a clearly stated question, problem or hypothesis. The selection of a study design appropriate to the task is the next key step. This paper provides guidance for the use of case report and case series designs by describing the 'what', 'when' and 'how' of both designs. Also described is the use of case reports and case series study designs in prehospital emergency research and the quality of published literature from 2000 to mid-2008.